Derivative Use by Romanian Banks After the EU Adhesion: A Financial Reporting Perspective - Maria Carmen Huian; Ciprian Apostol (CES Working Papers, 2014)
Romanian banks use derivatives to hedge against or speculate on the movement of economic variables such as foreign exchange rate or interest rate. To report these contracts, they apply the IFRS in both consolidated accounts (from 2007 onwards) and individual accounts (starting with 2012). This paper analyzes disclosures on derivatives for a 6-year period (2007- the year of the EU adhesion -2012) based on 132 financial statements available. The findings show that more than 72% of Romanian banks use derivatives, mostly for economic hedges and without much application of hedge accounting. Swaps are the most important contracts and foreign exchange risks the most protected against. On average, disclosures on derivatives follow the IFRS rules but provide little additional information beyond the minimum requirements which enables ambiguities and misinterpretations from users of the financial statements.
Keywords: M41; G21; 330; derivatives; financial statements; IFRS; hedge accounting Romania